Optical tomography with ultrasound localization for breast cancer diagnosis and treatment monitoring - Zhu, Quing (2007)
Optical tomography with ultrasound (US) localization utilizes co-registered ultrasound images to guide optical imaging reconstruction. A hand-held probe consisting of a commercial US transducer and near infrared optical imaging sensors of multiple wavelengths was used to simultaneously acquire US images and optical measurements. A novel image scheme was used to map the ultrasound-visible lesions for optical imaging reconstruction. As a result, we overcome the problem of intense light scattering caused by breast tissue and obtained reliable tumor hemoglobin concentration and blood oxygen saturation distributions from a group of patients. These functional parameters are valuable for aiding US diagnosis and assessing chemotherapy response.